Tinjauan Hukum Islam Tentang Penarikan Barang Jaminan Akibat Ketidakmampuan Nasabah Membayar Angsuran (Studi Kasus di Desa Mekarjaya Kec. Cikajang Kab. Garut) - Wati, Ai; Dewi, Cici Intania (Jurnal Hukum Ekonomi Syariah, 2022)
With the presence of companies engaged in lending goods or money, many people are interested in this matter. The buying and selling activities at CV. Mandiri should run smoothly because there has been an agreement between the Company and Prospective Customers or Consumers, meaning that the Company has entrusted its Customers or Consumers before conducting transactions with this Credit System. However, in practice, around 31% of Consumers are unable to repay their debts. As a consequence, according to the previous agreement, goods must be seized to be used as collateral to redeem their debt to CV. Mandiri. (1) What mechanism is used to seize collateral goods at CV. Mandiri, Kec. Cikajang? (2) What is the law regarding collateral at CV. Mandiri, Kec. Cikajang? The method used in this research is Qualitative Method. This means that the researcher directly enters the field. The conclusion of this research is that the seizure of collateral goods due to customers' inability to pay installments uses the theory of Maqashid al-Shariah, namely Hifzh Al-Din (preserving religion) and Hifzh Al-Mal (preserving wealth). Elaborating on Hifzh Al-Din and Hifzh Al-Mal, it is stated that without the consent of the collateral owner, the sale of the collateral cannot be done, and without the knowledge of the owner, the sale is not valid. After the seizure of the goods is completed, CV. Mandiri will auction the goods, and any excess from the auction proceeds will be returned to the customer. Keywords: Islamic Law, Collateral, Customer